Assessing the Effects of Solid Waste Dump Sites on the Quality of Water Resources: A Case Study of Kabale Municipality Dumpsite - Mutaawe, Bob Wamala (Kabale University, 2025)
The assessment of the effects of solid waste dump sites on the quality of water sources was done with the main objective of determining the possibility of contamination of the open and ground water sources by the resultant leachate from the municipal solid waste dump site at Kabalaga Hills in Kyanamira. The improper management of the leachate from the dump site accompanied with the uncontrolled access to runoff in the rainy season together with the impaired rainwater harvest system on the dump site structures makes it very vulnerable. This therefore makes the leachate easily carried away by the runoff from the rainwater and the water from the roof of the dump site structures and these get deposited in the stream of water and this is likely to the aquatic life in the stream as well as the other users such as the livestock farms in very close proximity as well as irrigation schemes. The study among other reasons was also carried out to characterize the leachate produced at the dump site, to characterize the neighboring water sources that included two gravity springs and a stream as well as identify any possible contamination and the most vulnerable to contamination of the water sources stated above. Water (collected from a radius of 1000m) and leachate samples were collected from spring one (317 meters from the dump site), spring two (608 meters from the dump site), a mainstream, River Rwabakazi (973m) as well as from the leachate collection pit present at the dump site using suitable sampling bottles. Some sample tests were done at the site while others were carried out at Mbarara National Water and Sewerage Corporation laboratory and among the tests that were done included pH, turbidity, electrical conductivity, TDS, TSS, BOD, and COD. These were compared with the WHO and Uganda standards for potable water. Conclusions and recommendations were drawn based on the results analysis that was done using charts and graphs from the resultant data that was obtained from the various site and laboratory analysis processes.